Technological entrepreneurship - Phan, Philip H. (Research in entrepreneurship and management., 2002)
Research in Management and Entrepreneurship is a thematic book series where each volume will focus on a single major issues in entrepreneurship. Volumes will not be published on any specific time table, but will be published when sufficient research interests exits to justify one. This series will focus on a specific emerging issue or on ones that could benefit from a consolidated, single source treatment. Thus, Research in Management and Entrepreneurship will be a comprehensive first source for academics, doctoral students and practitioners seeking information on selected topics. The papers in Research in Management and Entrepreneurship will be written by leading researchers and present the latest empirical and theoretical work on the topic selected. Contributions will cover a variety of perspectives from the various business disciplines as well as from allied fields such as economics, sociology and psychology. The volumes will be international in their coverage and the research presented will be balanced between developing and developed economies, where appropriate. The volumes will also have broader appeal that do academic journals because the literature can be fully reviewed and theoretical links more fully discussed.